2012
DOI: 10.1017/s0950268812000258
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological concordance of Japanese encephalitis virus infection among mosquito vectors, amplifying hosts and humans in India

Abstract: A temporal relationship of Japanese encephalitis virus (JEV) transmission in pigs, mosquitoes and humans revealed that sentinel pig seroconversions were significantly associated with human cases 4 weeks before (P = 0·04) their occurrence, highly correlated during the same time and 2 weeks before case occurrence (P < 0·001), and remained significantly correlated up to 2 weeks after human case occurrence (P < 0·01). JEV was detected in the same month in pigs and mosquitoes, and peaks of pig seroconversion were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…Domestic pigs serve as amplifying hosts for viruses while mosquitoes serve as the important vectors prior to transmission to humans (Borah et al 2013). Japanese encephalitis and Nipah viruses often affect pigs and pig-farm workers, as well as other pigfarming areas in Malaysia (Chua 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Domestic pigs serve as amplifying hosts for viruses while mosquitoes serve as the important vectors prior to transmission to humans (Borah et al 2013). Japanese encephalitis and Nipah viruses often affect pigs and pig-farm workers, as well as other pigfarming areas in Malaysia (Chua 2010).…”
Section: Introductionmentioning
confidence: 99%
“…JE is principally distributed in temperate and tropical areas of the Asia-Pacific Region, with an estimated worldwide annual incidence of nearly 70,000 clinical cases, resulting in upwards of 20,000 fatalities (4,5). Mosquitoes are the major vectors in JEV transmission in nature (6,7), but the interaction of JEV and the mosquito host, at the molecular level, is still unclear.…”
mentioning
confidence: 99%
“…28 More broadly, mosquito and virus surveillance systems combine vector data with climatic variables (temperature, rainfall, and tide height) and where appropriate sentinel animal seroconversions to create better calibrated predictive models of human disease risk. [34][35][36][37][38][39] In this study, we used a quantitative approach to assess individual mosquito trap sites in an attempt to improve and streamline surveillance. We found that mosquito abundance and RRV detection in mosquitoes were effective predictors of human RRV risk across the Peel region in south-west WA.…”
Section: Discussionmentioning
confidence: 99%